Microplastic stress induce bioresource production and response in microalgae: a concise review. Issue 1 (31st December 2022) - Ugya, Adamu Yunusa; Meguellati, Kamel; Aliyu, Abdulkadir Dauda; Abba, Abidina; Musa, Makiyyu Abdullahi
ABSTRACT: There are many literatures on the importance of bioresources from microalgae, but this review shows how microalgae are able to respond to the stress induced by microplastics (MP) and how the process leads to the production of bioresources. The study of these bioresources is significant because they are harnessed by man as energy and pharmaceutical tools. The extent of MP in the aquatic environment, microalgae stress induced by MP, the response of microalgae to stress induced by MP and bioresource production in microalgae due to stress induced by MP are described. The study shows that the presence of MP in the environment can induce nutrients and environmental stress, which enhances lipid accumulation and the production of other useful biotechnology resources. The study also shows that microalgae tend to produce resources that can respond to the stress induced by MP, which leads to a high removal efficiency of MP in aquatic ecosystems. The study also shows that the production of bioresources in the form of antioxidants, which are either enzymatic or non-enzymatic antioxidants, is the basic reason why microalgae are able to remove MP. A number of studies have shown the effect of MP on microalgae, while others have shown the efficiency of microalgae in the removal of MP from aquatic systems. But scanty literature exists showing how MP induces stress on microalgae. More studies are needed to show the mechanism and the concentration of bioresources produced by microalgae under the stress of MP.